Direct Oral to Parenteral Anticoagulants: Strategies for Inpatient Transition. (8th July 2020) - Lopez, Chelsea N.; Succar, Luma; Varnado, Sara; Donahue, Kevin R.
Abstract: The primary objective of this study was to describe the impact on bleeding rates of 2 different strategies for transitioning from a direct oral anticoagulant (DOAC) to a parenteral anticoagulant: a delayed, clinically driven strategy versus the standard per‐package‐insert strategy. This was a single‐center descriptive cohort study conducted at a large academic medical center. Included patients were 18 years or older, admitted as an inpatient, and had received at least 1 dose of a DOAC prior to initiation of therapeutic parenteral anticoagulation. The primary end point was the incidence of major bleeds on the transition from a DOAC to a parenteral anticoagulant via a standard versus an intentionally delayed strategy. The secondary outcomes evaluated renal function, reason for delay, DOAC anti–factor Xa concentration, international normalized ratio values, blood product administration, and thrombotic complications. A total of 300 patients were included. The primary end point of bleeding was higher in the delayed group than the standard group, 25% and 12%, respectively (odds ratio, 0.39; P < .05). In both groups, patients who bled had a higher severity of illness, a greater incidence of acute kidney injury, and, when available, higher median DOAC anti–factor Xa concentrations. Despite a more conservative approach, patients in the delayed group experienced more bleeding, most likely attributable to a higher severity of illness, which highlights emerging challenges of inpatient anticoagulation management. Further prospective studies analyzing DOAC pharmacodynamics and pharmacokinetics in acutely ill patients are warranted.